GAMBARAN FAKTOR PENDUKUNG DAN PENGHAMBAT PELAKSANAAN REKAM MEDIS DI PUSKESMAS MULYOREJO - Meyva Nilam Fatchulloh; Putri Kusuma Wijayanti; Muhammad Roy Saputra; Lilis Masyfufah; Shobah Fajriyati (Journal of Innovation Research and Knowledge, 2025)
Electronic Medical Records (RME) greatly facilitate the improvement of service quality at the Mulyorejo Health Center, but it cannot be denied that there will always be supporting factors and hindering factors that accompany during the process. Supporting and inhibiting factors that are researched in the implementation of this Medical Record, using the 5M method, namely Man, Material, Machine, Methode, Money. This research was conducted at the Mulyorejo Health Center in Surabaya. The purpose of this study is to provide an overview of supporting and inhibiting factors, in order to add insight and provide suggestions for the implementation of better medical records. This research method uses qualitative descriptive. Data collection techniques by observation and interview. The research results show that there are still obstacles experienced when providing services to patients, for example in Human Resource Planning (SDM), Puskesmas Management Information System (SIMPUS) and E-Health, the last one is in Puskesmas reporting